Tramadol Abuse Among Adolescents: Analysis Based on Differential Association Theory in Tasikalaya Regency - Pirdaus, Dede Irman; Ibrahim, Riza Andrian; Yuningsih, Siti Hadiaty (International Journal of Health, Medicine, and Sports, 2024)
Adolescents in Tasikalaya District show a tendency to be susceptible to Tramadol protection, a type of opioid analgesic commonly used to reduce moderate to severe pain. This phenomenon is a resource for the medical community, health practitioners, local governments and other related parties. Serious attention is needed to this problem to prevent negative impacts on the health and welfare of adolescents in the region. Coordinative efforts between the health, education and government sectors need to be strengthened to develop effective prevention and intervention strategies. A deep understanding of the factors driving Tramadol is key in designing appropriate preventive measures. This research examines the use of the drug tramadol among teenagers in Tasikalaya Regency using a qualitative approach and Differential Association Theory. The results of the study showed that adolescents' support for tramadol was caused by social and environmental factors, including interactions with peers and family members who also used the drug. Teenagers often rationalize their behavior and have certain attitudes that influence their decision to take tramadol. Apart from that, the easy availability of tramadol medication and affordable prices also influences teenagers' choices. This study provides a deeper understanding of the problem of tramadol among adolescents and suggests comprehensive preventive measures.